Secure outsource computing scheme of modular exponentiation based on single server - Weijie DING (Dianxin kexue)
At present,in discrete-log based cryptographic protocols,most of the computational models of modular exponentiation are for primes,while less work has been done for composite.What’s more,most schemes are based on two servers,in which it requires at least one server to be honest.However,there may not be a fully trusted cloud server in the actual environment.Then a new secure method for outsourcing exponentiation modular a composite which based on a single server was proposed.The scheme used a new mathematical division method,it could ensure the privacy of the base and exponentiation.Compared with the existing schemes,the checkability of our scheme can be greatly improved.The user can detect the error result with the probability of 119/120.